Efecto citotóxico del extracto etanólico de hojas de annona cherimola en una línea celular de cáncer de colon humano en medio de cultivo con pH neutro - Loján Medina, Karen Priscila (2015)
The experimental investigation covers new and innovative themes that help finding more effective, economic and natural methods to treat some diseases as well as in the case of colon cancer, in which the body produces an excess of unusual cell growth and multiplication; invading the surrounding tissues of the large intestine, to its junction with the rectum, causing long term metastasis via the lymphatic or hematic leading to tumors in other organs. So we focus on developing the present experimental and conducting prospective research studies of cytotoxic effect of etanolic extract from the leaves of Annona Cherimola cell lines of colon cancer in culture medium with neutral pH. In this research study techniques applied as trypsinization and incubation processes for subculturing and maintaining tumor cells, in addition to methods of cell viability by trypan blue staining and observation in a Neubauer chamber, while determining cell proliferation by observing the confluence of tumor cells, procedures by which we obtained results of cell viability demonstrating the percentage of cell death of the tumor cell lines of colon cancer of 88.1% with the ethanol extract at highest concentration at 72 hours in the degree of cell proliferation we obtained results of 17% with the concentrated extract at the same times, which show that if we obtained cell death and lower confluence in tumor cells, thus achieving determine the cytotoxic effect produced by the ethanol extract the leaves of Annona Cherimola in tumor cells used, however the door open to further research that will help better determine the cytotoxic effect of all components of this plant in various types of cancer is still left. Key Words: Cancer, Annona Cherimola, extract, experimental cytotoxic.